Synecdochic and metonymic chains in the organizing narratives of PRC forensic genetic research targeting Uyghurs in Xinjiang - Munsterhjelm, Mark (Public Journal of Semiotics, 2025)
In this paper, I demonstrate how synecdochical and metonymic chains function in the semiotic narrative schema of forensic genetics articles. Greimas’s narrative schema and work on categories provides a framework that can be synthesized with cognitive linguistic advances on synecdoche and metonymy chains to understand how meaning is created in organizational interactions through the circulation of objects of value. Based on an empirical analysis of controversial forensic genetic articles involving Uyghur subjects on ancestry inference marker and phenotype (visible appearance) inference marker research projects, it shows how scientists from the Chinese Ministry of Public Security and other scientists organize through a shared manhunting narrative schema. In this schema, Society and/or Humanity send scientists quests to protect society by improving forensic genetic technologies to variously track down and capture or kill criminals, separatists, insurgents and terrorists. Utilizing recent advances in theorization of synecdoche, the article shows how synecdoche functions in the categorization of Uyghurs as “Eurasian” and “mixed East Asian and European” populations. It also shows how synecdoche and metonymy function through syllogisms to mediate relations and the exchange of objects of value such as Uyghurs’ genetic materials and data between the phases and sub-narratives of the scientific articles’ narrative schema.